Asuhan Keperawatan pada Pasien Stroke Riwayat Penyakit Diabetes Mellitus dengan Gangguan Mobilitas Fisik - Ernaningrum, Diah Ayu; Hartanto, Agung Eko; Wiratmoko, Heru (Universitas Sultan Ageng Tirtayasa, 2024)
Stroke is a neurological deficit that disrupts the blood supply to the brain can occur due to several pathological conditions including atherosclerosis. Diabetes mellitus is one of the causes of stroke where high blood glucose levels can accelerate atherosclerosis. One of the signs of stroke symptoms is a decrease in muscle strength which can lead to impaired physical mobility. One of the efforts to overcome is to train ROM. The purpose of the study was to determine how nursing care for stroke patients with a history of diabetes mellitus with impaired physical mobility.az The case study design in this study uses qualitative descriptive research with a case study approach. After carrying out nursing care for 7 days, the results of research on physical mobility disorders in Mr. P were obtained. P has improved as evidenced by using the MMT instrument on muscle strength, namely from scale 2 to scale 4 (mild physical mobility impairment). For the range of motion has increased, namely a scale of 25 to 46, which is from a range of motion enough to good. ROM training is very important because it affects muscle contraction and relaxation so that it can facilitate blood flow so as to increase muscle strength. Suggestions for stroke patients with a history of diabetes mellitus are expected to routinely do ROM exercises and do health checks, namely blood pressure and glucose levels.